KEKUATAN PEMBUKTIAN AKTA DI BAWAH TANGAN YANG DILEGALISASI OLEH NOTARIS (Studi Putusan Nomor:201/Pdt.G/2014/PN.Pbr) - Wanty Agustina; Maryati Bachtiar; Ulfia Hasanah (Jurnal Online Mahasiswa (JOM) Bidang Ilmu Hukum, 2018)
Basically the position of a deed under the hand that is legalized by a deed under the hands that is not legalized is equally not an authentic deed in terms of proof. but when it is associated with the veracity of the signature, the deed under the legalized hand is stronger than the undocumented deed under the hand. This is because the signing of the certificate under the legalized hand is done before a notary public official who is authorized to do so.The type of research used in the writing of this law is empirical sociological law research is a method or method used in legal research conducted by examining the existing library materials by looking at events or facts that occur in the social environment. The nature of this research is descriptive. This study uses secondary data that is ready-made data.The result of this research is the strength of proof of the deed under the hand that is legalized before the notary (study decision number 201 / Pdt.G / 2014 / Pn.Pbr) is not the same as the authentic deed because it can still be denied the truth and must prove its truth through the evidence other or witnesses. The Notary guarantees the certainty of the date of the deed and the signatures of the parties, but is not liable for the contents of the deed. Deed under hand has no authenticity and has no executorial power. Where a deed under a new hand is valid if the signing party recognizes the signature. The responsibility of a notary to a legalized deed that is legalized before him (Study Decision number: 201 / Pdt.G // 2014Pn.Pbr) is about the certainty of the signature that it is certain that the signature is indeed a party to the agreement, not someone else. It is said that because the legalization of the letter is required to know the person who signed it by looking at his identification such as Identity Card and others. If the legalized person knows the right person, then they put their signature before the legalized at that time, day and date.Keywords: proof, deed under the hand